The Science Performance of JWST as Characterized in Commissioning. (1st April 2023) - Rigby, Jane; Perrin, Marshall; McElwain, Michael; Kimble, Randy; Friedman, Scott; Lallo, Matt; Doyon, René; Feinberg, Lee; Ferruit, Pierre; Glasse, Alistair; Rieke, Marcia; Rieke, George; et al.
Abstract: This paper characterizes the actual science performance of the James Webb Space Telescope (JWST), as determined from the six month commissioning period. We summarize the performance of the spacecraft, telescope, science instruments, and ground system, with an emphasis on differences from pre-launch expectations. Commissioning has made clear that JWST is fully capable of achieving the discoveries for which it was built. Moreover, almost across the board, the science performance of JWST is better than expected; in most cases, JWST will go deeper faster than expected. The telescope and instrument suite have demonstrated the sensitivity, stability, image quality, and spectral range that are necessary to transform our understanding of the cosmos through observations spanning from near-earth asteroids to the most distant galaxies.